(untitled) - Emblemsvag, Jan (Hoboken, N.J., 2003)
The book helps organizations apply knowledge about past performance and risks to make meaningful predictions about costs and risks associated with products, processes, and organization.
Keywords: Costs, industrial,Life cycle costing,Risk management,Rủi ro trong quản trị